Facilitating HIV/AIDS and HIV testing literacy for emergency department patients: a randomized, controlled, trial - Merchant, Roland C. (BMC Emerg Med, 2018)
BACKGROUND: Although this has not been fully studied, videos and pictorial brochures might be equivalent methods of delivering HIV/AIDS and HIV testing information to emergency departments (ED) patients. It also is not known how well or for how long such knowledge is retained, if this information should be tailored according to patient health literacy, and if retention of this knowledge impacts future HIV testing behavior. METHODS: We will conduct a multi-site, randomized, controlled, longitudinal trial among 600 English- and 600 Spanish-speaking 18–64-year-old ED patients to investigate these questions. We will stratify our sample within language (English vs. Spanish) by health literacy level (lower vs. higher) and randomly assign patients to receive HIV/AIDS and HIV testing information by video or pictorial brochure. All patients will be tested for HIV in the ED. At 12-months post-enrollment, we will invite participants to be tested again for HIV. As primary aims, we will compare the efficacy of pictorial brochures and videos in improving short-term (in ED) HIV/AIDS and HIV testing knowledge and retaining this knowledge over 12 months. We will determine if and how short-term improvement and longer-term retention of knowledge interacts with information delivery mode (pictorial brochure or video), patient health literacy level (lower or higher), and language (English or Spanish). As secondary aims, using the Information-Motivation-Behavioral Skills (IMB) model as a heuristic framework, we will measure constructs from the IMB model relevant to our study, and assess their impact on HIV re-testing behavior; we will also examine the moderating influences of information delivery mode, language, and health literacy level. In addition, we will explore simplified screening strategies to identify ED patients with lower health literacy as ways to implement a tailored approach to HIV/AIDS and HIV testing information delivery in EDs. DISCUSSION: Study findings will guide ED-based delivery of HIV/AIDS and HIV testing information; that is, whether delivery modes (video or pictorial brochure) should be selected for patients by language and/or health literacy level. The results also will inform EDs when, how, and for whom information needs to be provided for those undergoing testing again for HIV within a one-year period. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02284451. Posted November 6, 2014. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12873-018-0172-7) contains supplementary material, which is available to authorized users.